2012
DOI: 10.5539/elt.v5n9p144
|View full text |Cite
|
Sign up to set email alerts
|

A Think-aloud Protocols Investigation of Saudi English Major Students’ Writing Revision Strategies in L1 (Arabic) and L2 (English)

Abstract: This study investigates the writing revision strategies used by 16 Saudi English as foreign language (EFL) students. Two research methods were employed. First, think-aloud reporting was used to gain insightinto the thought processes utilized by the students, and to study the revision strategies that Saudi maleuniversity students make use of while writing compositions in L1 Arabic and L2 English. Second, a semi-structured interview was conducted with the aim of supporting the think-aloud data. Analysis of the t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
2
10
0
Order By: Relevance
“…Our findings, and constant with what other researchers affirmed (Alhaisoni, 2012;Al-Semari, 1995;Al-Sharah, 1997), could be useful for students with low language proficiency. As Raimes asserted, "think-aloud composing for ESL composition research…can be applied…to generate words, sentences, and chunks of discourse and to communicate in the new language."…”
Section: Resultssupporting
confidence: 70%
“…Our findings, and constant with what other researchers affirmed (Alhaisoni, 2012;Al-Semari, 1995;Al-Sharah, 1997), could be useful for students with low language proficiency. As Raimes asserted, "think-aloud composing for ESL composition research…can be applied…to generate words, sentences, and chunks of discourse and to communicate in the new language."…”
Section: Resultssupporting
confidence: 70%
“…L2 writing research also examined the link between L1 and L2 writing strategies L1 writing strategies (Alhaisoni, 2012;Whalen & Menard 1995). Research indicates that there is a link between the L1 and L2 strategies, though there are some inclusive research findings.…”
Section: Writing Strategiesmentioning
confidence: 99%
“…Previous research has shown that factors such as motivation, attitude, and language strategy influence L2 learning. Although considerable number of studies have investigated howwriting strategies are related to writing proficiency (Chien, 2012;Mu, 2005;Raimes, 1985;Sasaki, 2002;Victori, 1999), goal orientation (He, 2005), writing performance (McMullen, 2009;Nguyen & Gu, 2013) L1 writing strategies (Alhaisoni, 2012;Cumming et al, 1989;Whalen & Menard, 1995), and learning context (Leki, 1995, Sasaki, 2004, 2007Wong, 2005), little research has explored the writing strategies of undergraduate studentsin second language learning contexts. Furthermore, very few qualitative studies have focused on documenting the types of language learning strategies particularly L2 writing strategies among foreign /second language learners.…”
Section: Introductionmentioning
confidence: 99%
“…SLA researchers also investigated how L1 writing strategy use is related to L2 writing strategies (Alhaisoni, 2012;Cumming et al, 1989;Keck, 2006;Skibniewski, 1988;Whalen & Menard, 1995). With few exceptions, research targeting the relationship between L1 and L2 writing strategies reveals that L1 writing strategy useis closely associated with L2 writing strategies.…”
Section: Introductionmentioning
confidence: 99%